Willingness to treat COVID-19 disease: What do medical and nursing students perceive? - Cheah, Whye Lian; Francis Wing, C.B.; Zahari, A.N.; Idris, A.S.; Maksul, N.A.A.; Yusman, N.A.L.; Johns, W.E. (Elsevier, 2021)
Background.- The COVID-19 pandemic has resulted in many changes in the delivery of health service which not only affect the public as well as healthcare workers, and also among medical and nursing students who are currently undergoing their training. This study aims to determine the commitment and willingness of medical and nursing students in Sarawak in treating patients with COVID- 19 and its associated factors. Methods.- It was a cross-sectional study using online questionnaire, carried out in a public university in Sarawak, Malaysia. All medical and nursing students were invited to participate in this study. Data was entered and analysed using IBM SPSS version 22. Result. – A total of 304 respondents participated in the study, with 81.6% female and 69.4% medical students. Majority of the respondents were most willing to take a medical history, do a physical examination, throat swabbing, draw blood and perform IV drip insertion. There was a high commitment among respondents to treat COVID-19 patients regardless of personal risks. Majority of the respondents also agreed that medical staff who are involved in treating COVID-19 patients should be receiving a salary increase and compensation should be given to affected healthcare families, and all non-medical staff should be involved in treating COVID-19 patients. About 71% agreed about a law mandating medical staffs to treat patient. Conclusion. - The willingness and commitment of medical and nursing students to treat COVID-19 patients was high, indicating their potential work force as healthcare providers.